2015
DOI: 10.3390/ma8084884
|View full text |Cite
|
Sign up to set email alerts
|

Bone Regeneration and Remodeling within a Unidirectional Porous Hydroxyapatite Bone Substitute at a Cortical Bone Defect Site: Histological Analysis at One and Two Years after Implantation

Abstract: Unidirectional porous hydroxyapatite (UDPHAp) is an artificial bone substitute with a unique microstructure consisting of 100–300-µm oval pores that present the material unidirectionally. UDPHAp has a compression strength of 14 MPa and a porosity of 75%, which promotes cell migration and capillary formation within the material. Despite these advantageous properties, bone remodeling and bone formation with UDPHAp remain unclear. To examine long-term remodeling and differences in bone formation based on the defe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 15 publications
(19 reference statements)
0
22
0
Order By: Relevance
“…Iwasashi et al analyzed bone formation within UDPHAp blocks implanted into the same animal bone defect model used in the present study and found that bone formation was greater in the cortical regions of the UDPHAp compared to medullary areas. Consistent with this previous finding, more lacunae and osteon‐like structures were found in the cortical areas in the present study.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Iwasashi et al analyzed bone formation within UDPHAp blocks implanted into the same animal bone defect model used in the present study and found that bone formation was greater in the cortical regions of the UDPHAp compared to medullary areas. Consistent with this previous finding, more lacunae and osteon‐like structures were found in the cortical areas in the present study.…”
Section: Discussionmentioning
confidence: 57%
“…In a previous study, we implanted UDPHAp blocks into a rectangular cortical bone defect in rabbit tibia and reported statistically greater new bone formation after 12 weeks in cortical areas than in the medullary cavity . This difference of bone growth between the cortical area and medullary cavity was also observed throughout the 2‐year period of recovery . Based on these findings, we speculated that the unique structure of UDPHAp promotes cortical bone formation under the mechanical stress of weight bearing.…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…Numerical simulation was performed using FEM software COMSOL Multiphysics v.5.2.®. The geometry model is similar to the fragment of rabit tibia investigated in experimental work performed by Iwasashi et al [19]. A 4.5 mm × 7 mm rectangular defect was made in proximal tibia of rabbit and then fitted with a piece of rectangular prism of porous biomaterial.…”
Section: Numerical Simulationmentioning
confidence: 99%
“…The simplest structure of scaffold with mechanical optimization is the unidirectional porous structure where continuous pores and struts are constructed in the loading direction. Actually, this kind of unidirectional porous structure has effectively been utilized for a bone substitute, where bone growth takes place in the direction of the pores and maximized stiffness and strength are obtained in that direction [1], [2].…”
Section: Introductionmentioning
confidence: 99%